Spouse's participation in perinatal care: a qualitative study - Nahid Mehran; Sepideh Hajian; Masoumeh Simbar; Hamid Alavi Majd (BMC, 2020)
Abstract Background Pregnancy is one of the most important periods of any woman's life, wherein the support of her relatives, especially her spouse, enables her to tolerate the difficulties with good memories. However, in Iran, there are very few studies on the participation of spouses in the perinatal period. Therefore, the present study aimed to explain the concept of spouse participation in perinatal care. Methods This is a qualitative study that was carried out in 2018 on spouse participation in perinatal care in Qom, Iran. Purposive sampling from pregnant or postpartum women, spouses, midwifery care providers, and key informants was performed according to study inclusion criteria. Semi-structured in-depth interviews were carried out until the data saturation was met. Also, the data analysis was performed based on a conventional content analysis approach according to Graneheim & Lundman steps using MAXQDA software (v.10). Five Guba and Lincoln criteria were applied to ensure the trustworthiness of data. Results Fifty-three final codes were classified into 18 sub-categories, 7 categories, and 3 themes including empathy (emotional and cognitive understanding), accountability (supporting, position management, compassion), and consequences (help improvement of family function, improvement of maternal-neonatal health). Conclusions Based on the findings of this study, the concept of men's participation in this period has been defined as a set of empathic and responsive behaviors that can lead to improvement of the family function and mother and baby health.